2013
DOI: 10.1088/0143-0807/35/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

A new introductory quantum mechanics curriculum

Abstract: The Institute of Physics New Quantum Curriculum consists of freely available online learning and teaching materials (quantumphysics.iop.org) for a first course in university quantum mechanics starting from two-level systems. This approach immediately immerses students in inherently quantum mechanical aspects by focusing on experiments that have no classical explanation. It allows from the start a discussion of interpretive aspects of quantum mechanics and quantum information theory. This article gives an overv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 29 publications
0
75
0
3
Order By: Relevance
“…The targets for these activities are junior-or seniorlevel introductory quantum mechanics students, particularly those in "spins-first" courses. [6][7][8][9] The game also may be played before students learn the theory of quantum states and measurements as a qualitative introduction to these topics, for example as a teaser activity for a sophomore-level modern physics survey course 12,20 or an introductory quantum computing course for nonphysicists. 21 Students who understand quantum measurements will also benefit because the core of the game is a foundational and subtle question: How much infor-mation can we gain from a single quantum measurement?…”
Section: Learning Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The targets for these activities are junior-or seniorlevel introductory quantum mechanics students, particularly those in "spins-first" courses. [6][7][8][9] The game also may be played before students learn the theory of quantum states and measurements as a qualitative introduction to these topics, for example as a teaser activity for a sophomore-level modern physics survey course 12,20 or an introductory quantum computing course for nonphysicists. 21 Students who understand quantum measurements will also benefit because the core of the game is a foundational and subtle question: How much infor-mation can we gain from a single quantum measurement?…”
Section: Learning Objectivesmentioning
confidence: 99%
“…6,7 This "spins-first" approach aims to teach quantum axioms in mathematically simpler finite Hilbert spaces before bringing in the complications of solving the wave equation. 8,9 This article describes: a simple two-level quantum system, how to simulate measurements on this system using a classical random number generator (RNG) such as dice rolls, and a two-player competitive game using this simulation. Although many excellent teaching-focused computer simulations of quantum mechanical systems, 10 and specifically two-level systems, [11][12][13][14] exist, the exercise here takes a different approach.…”
mentioning
confidence: 99%
“…Indeed, several prior studies have found that many advanced students struggle with the foundational issues in quantum mechanics including measurement (e.g., see [1][2][3][4][5][6][7][8][9][10][11][12]). Studies have focused on diverse pedagogical approaches for helping students learn quantum mechanics better (e.g., see [13][14][15][16][17][18][19][20][21][22][23][24][25][26]), and visualization tools such as QuVIS and QuTIP have been developed to help students develop intuition about quantum mechanical phenomena [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties and misconceptions in learning such topics are well known and very often described [15,16]. Recent papers proposing novel approaches are still devoted to reduce such difficulties [17][18][19].…”
Section: Introductionmentioning
confidence: 99%